Advances in the Theory of Control, Signals and Systems with Physical Modeling - Levine, Jean; Müllhaupt, Philippe (Lecture Notes in Control and Information Sciences, 2011)
In the 60's, control, signals and systems had a common linear algebraic background and, according to their evolution, their respective backgrounds have now dramatically differed. Recovering such a common background, especially in the nonlinear context, is currently a fully open question. The role played by physical models, finite or infinite dimensional, in this hypothetical convergence is extensively discussed in this book. The discussion does not only take place on a theoretical basis but also in the light of two wide classes of applications, among the most active in the current industrially oriented researches: - Electrical and Mechatronical systems; - Chemical Processes and systems appearing in Life Sciences. In this perspective, this book is a contribution to the enhancement of the dialogue between theoretical laboratories and more practically oriented ones and industries. This book is a collection of articles that have been presented by leading international experts at a series of three workshops of a Bernoulli program entitled "Advances in the Theory of Control, Signals and Systems, with Physical Modeling" hosted by the Bernoulli Centre of EPFL during the first semester of 2009. It provides researchers, engineers and graduate students with an unprecedented collection of topics and internationally acknowledged top-quality works and surveys.